Effects of dietary microalgae (Schizochytrium spp.) supplement on milk performance, blood parameters, and milk fatty acid composition in dairy cows - Liu, Gaofei; Yu, Xiong; Li, Shengli; Shao, Wei; Zhang, Nan (Czech Journal of Animal Science, 2020)
The objective of this study was to examine the effects of dietary inclusion of microalgae (Schizochytrium spp.) on milk yield, milk composition, and docosahexaenoic acid (DHA) transfer efficiency in dairy cows. Thirty-six lactating Chinese-Holstein dairy cows were randomly allocated to three treatment groups (n = 12; 0, 170, and 255 g microalgae supplement per day) in a 60-day experimental period. No significant treatment effect was observed on DMI and milk performance. Similarly, there was no significant microalgae supplement effect on blood haematological and biochemical parameters, except for platelets (P < 0.01) and thrombocytosis (P < 0.01), suggesting that the inclusion of microalgae in dairy cow diets would not affect production performance and animal health. Compared to the control group, adding 170 and 255 g microalgae to diets significantly increased the proportion of linoleic acid, DHA, n-3 and n-3/n-6 ratio in the blood (P < 0.05). Consequently, DHA concentration and n-3/n-6 ratio were increased in milk, indicating that the milk fatty acid composition could be affected by nutritional manipulation. The overall DHA transfer efficiency was 10.1% and 11.3% for 170 and 255 g microalgae supplement, suggesting that the addition of microalgae to dairy cow diets is a feasible strategy to produce DHA enriched milk in practice.
Keywords: bovine; docosahexaenoic acid; microalgae; production performance